Faktor-Faktor Yang Berhubungan Dengan Jumlah Perdarahan Pada Ibu Bersalin - St. Surya Indah Nurdin; Rusli A Katili; Yuliandary Yunus; Andi Nur Aina Sudirman; Tressan Eka Putri S. Katili (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Childbirth bleeding remains one of the leading causes of maternal morbidity and mortality. Identifying factors associated with the amount of blood loss during childbirth is essential for developing more effective prevention strategies. This study aimed to analyze factors associated with the amount of childbirth bleeding among women delivering at Sitti Khadijah Hospital, Gorontalo. A cross-sectional design was employed using secondary data obtained from medical records. A total of 195 mothers who delivered vaginally were selected through simple random sampling. The results showed that maternal age and perineal rupture were significantly associated with the amount of childbirth bleeding in the bivariate analysis. However, after multivariable adjustment, only perineal rupture remained significantly associated with the amount of childbirth bleeding (β = 22.28; p = 0.018). Mothers who experienced second-degree perineal rupture tended to have a higher amount of blood loss compared with those with an intact perineum. In conclusion, perineal condition during childbirth is an important factor associated with increased blood loss during delivery. Efforts to prevent and appropriately manage perineal rupture should be strengthened in midwifery care to improve maternal safety.